Performance enhancement of a hybrid AC-DC microgrid operating with alternative energy sources using supercapacitor - Jayalakshmi, N. S. (Array, 2021)
Microgrids with non-conventional energy sources have become popular recently. Hybrid AC-DC microgrid (HMG) architecture is effectual as it avoids several power conversions for the consumers. Therefore, this article presents a comprehensive study on grid-tied HMG with PV array and wind energy conversion system (WECS) as principal sources. Fuel cell (FC) acts as the auxiliary source in the DC subgrid and the supercapacitor (SC) is used for instantaneous energy management. The hydrogen storage system is used to store surplus power produced by the PV array. The power flow between the subgrids is regulated using the interlinking converter (ILC) by a PQ controller. The main contribution of this article is the comparative investigation of system operation in the HMG configuration in the presence and absence of a supercapacitor bank on the DC bus. The maximum DC bus voltage fluctuation during load variations in the absence and presence of SC bank is found to be 6.6 V and 3.9 V respectively. Similarly, the maximum transient fluctuation in the power supplied to the DC load is found to be 830 W in the absence of SC bank and 340 W in the presence of SC bank.